Toby's Surprise (London Dean & Son : Egmont, 2014)
Six board books based on favourite characters and stories from the Thomas & Friends TV series: Thomas and Diesel; Steady Old Edward; Excellent Emily; Gordon's Shortcut; Rosie and the Special; and Toby's Surprise. The pictures on the back covers of the books make up a big, colourful picture when placed side-by-side!
English stories
2
Keywords: English stories